Implicaciones jurídicas entre fideicomiso civil, la fiducia mercantil, y la inembargabilidad de la propiedad en el territorio colombiano (2018)
The present work called "Legal Implications of Civil Trust Property for the protection of heritage", focuses on a tool, legal, that is increasingly being welcomed by those who want to insure their assets, however there is a flaw, as is the lack of knowledge and / or clarity in the development of the procedure by lawyers and notaries. The study is framed in a qualitative paradigm. With a documentary Bibliographic focus and critical analysis. The information collection technique was the normative and documentary review. Among the main results it is highlighted: The Civil Trust, despite being a regulated figure in the Civil Code, is currently classified as a novel and innovative subject, and highly recurrent by individuals, among others. Given the aforementioned, it should be a reason for study, analysis and legal academic discussion, which allow a greater knowledge and development of the subject. It is necessary to analyze the formation of the legal programs, the recognition and normative appropriation of the legal figure of the Civil Trustee, as well as the procedural aspects for its application. In the same way, processes of legal updating in this specific field should be carried out, for lawyers and notaries, in such a way that it has greater applicability of said tool and does not leave it as a dead letter.